IMPLEMENTASI FUZZY AHP DAN TOPSIS PADA PEMILIHAN METODE PEKERJAAN PERKERASAN KAKU - Agung Budi Broto; Ester Maharani (Prokons: Jurnal Teknik Sipil, 2021)
Abstract Rigid Pavement is the main work in toll road construction. In the implementation of rigid pavement, there are several alternatives, namely mechanical and conventional, where each alternative has advantages and disadvantages. This study aims to determine the selection of appropriate work methods on the Kunciran - Cengkareng Toll Road Project. Many multi-criteria must be considered, the consideration of decision making can be done by using the Technique For Others Preference By Similarity To Ideal Solution (TOPSIS) method and Fuzzy Analytical Hierarchy Process (FAHP) which can give weight to the specified criteria. The objectives of this study are: (1) to find out the most influential criteria as a basis for considering the selection of methods for implementing rigid pavement works. (2) to determine the method of implementing rigid pavement work that is appropriate by the existing criteria. This study uses a questionnaire survey. The results of this study indicate that the criteria for quality of work are the most influential criteria with a value of 0.351, then the implementation time criteria (0.201), the criteria for work costs (0.150), work safety criteria (0.133), work volume criteria (0.084), implementation process criteria (0.049), and the last is the implementation preparation criteria (0.032). The appropriate alternative used for the rigid pavement method is the mechanical method with a value of 0.621, while the mechanical method only reaches the values of 0.379.. Keywords: Fuzzy AHP; Perkerasan Kaku; TOPSIS.